A PARTICIPATION FOR STRENGTHENING COMMUNITY MODEL FOR SUSTAINABLE DEVELOPMENT - Jarutirasarn, Piyachat; Junhasobhaga, Jumnian; Sanont, Rujikarn; Samantreeporn, Saowanee (CENTRAL ASIA AND THE CAUCASUS, 2022)
The objectives of this article were (1) to analyze community contexts, (2) to analyze participation in strengthening communities for sustainable development, and (3) to present a model of participation in community development to strengthen communities for sustainable development. The study found that the community was affected by all aspects including socio-economic development, technology development, environmental problems, and natural disasters from climate change. Especially, stepping into the 4th Industrial Revolution with artificial intelligence (AI) caused the disruption in all aspects. Community participation consisted of 4 aspects; decision making, operation, receiving benefits and evaluation. For a model of community participation, all parties must be people-centered. People development to develop communities applied the principle of participation in holistic collaborative learning. Recognizing the benefits of information technology and AI was applied as an important tool in processing and synthesizing the information. The development was based on the philosophy of Sufficiency Economy.